Strategi Koping Masyarakat Jawa di Masa Pandemi COVID-19 - Faruq Faruq; Hanum Midya Syahrina; Nureyzwan Sabani; Siti Rahmawati; Laksmy Dewi Sukmakarti; Nanik Prihartanti (Mudra Jurnal Seni Budaya, 2022)
The COVID-19 pandemic or in Javanese terms "pageblug" has caused problems experienced by people in Indonesia, especially the Javanese. Problems that arise must be handled appropriately so as not to have a negative impact on people's daily lives, one effective way is with a coping strategy. This research uses qualitative methods to understand the meaning of social phenomena experienced by individuals or communities with the focus of the research on coping strategies for the Javanese society affected by the COVID-19 pandemic. The data collection technique in this research used an open ended-questions regarding coping strategies distributed through google form media. The subjects of this research amounted to 100 Javanese respondents who live in the residency of Surakarta (Surakarta City, Karanganyar Regency, Sragen Regency, Wonogiri Regency, Sukoharjo Regency, Klaten Regency, and Boyolali Regency) for at least 2 years, which are divided into 2 categories of adult respondents, 76 early-adult respondents and 24 middle-adult respondents. The data that has been obtained were analyzed using thematic analysis. The results of this research show that the coping strategies implemented by the Javanese society during the COVID-19 pandemic are: Never Give Up (Tangguh), Obey the Rules (Tumut), Be Patient, Grateful and Accept the Situation (Narimo ing pandum), Calm & Not Anxious, Maintain Health, and Live Frugally (Gemi nastiti). The implementation of coping strategies can be applied by the Indonesian society, especially the Javanese society in dealing with the pandemic.